Determinants of income inequality - Akhsyim Afandi; Vebryna Permatasari Rantung; Hazem Marashdeh (Universitas Islam Indonesia, 2017)
This study examines whether changing economic structure, social conditions, and financialization are responsible for increased income inequality in Indonesia. By employing panel data of 32 provinces in Indonesia that spans from 2007 to 2013, it finds that structural change affects income inequality, increased share of finance reduces inequality, which is against the financialization hypothesis, and social conditions have expected effects on income inequality. While an increased share of both agriculture and service sectors tends to reduce inequality, an increased share of manufacture sector has no effect on inequality. This study finds that falling poverty increases inequality, implying that policy to reduce poverty might not be neutral for inequality and instead cannot prevent it from increasing. Since the higher the college participation rate the higher income inequality tends to be, it does not automatically imply that in order to reduce inequality we need to reduce the number of people who go to college. It might be the case that the college participation rate has not reached a turning point, below which its increase increases inequality, but beyond which its increases reduces inequality.